Polyvinyl Acetal Resin
A tailored polyvinyl acetal resin with controlled molecular weights and peak integral values addresses viscosity changes and sheet attack issues, ensuring stable performance in high ethanol solvents for multilayer ceramic capacitors.
Patent Information
- Application Number
- JP2024092158
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2024-06-06
- Publication Date
- 2025-01-14
- Estimated Expiration
- 2044-05-22
AI Technical Summary
Existing polyvinyl acetal resins used as binders for ceramic slurry in multilayer ceramic capacitors face issues with viscosity changes when using solvents with a high proportion of ethanol, leading to environmental concerns due to toluene toxicity and sheet attack problems.
A polyvinyl acetal resin with specific molecular weight distributions and peak integral values, adjusted through controlled acetalization conditions, maintains low viscosity variation and enhances sheet attack resistance even with high ethanol solvents.
The resin achieves stable viscosity and improved sheet attack resistance, enabling the production of reliable multilayer ceramic capacitors with enhanced performance.
Smart Images

Figure 0007612929000006 
Figure 0007612929000001 
Figure 0007612929000002
Abstract
Description
[Technical field]
[0001] The present invention relates to a polyvinyl acetal resin, a slurry for a ceramic green sheet, a ceramic green sheet, and a multilayer ceramic capacitor. [Background technology]
[0002] 2. Description of the Related Art In recent years, electronic components mounted in various electronic devices have become smaller and more laminated, and laminated electronic components such as multilayer circuit boards, laminated coils, and laminated ceramic capacitors are widely used. Among them, multilayer ceramic capacitors are generally manufactured through the following steps. First, a plasticizer, a dispersant, etc. are added to a solution in which a binder resin such as polyvinyl butyral resin or poly(meth)acrylic acid ester resin is dissolved in an organic solvent, and then a ceramic raw material powder is added and mixed uniformly with a mixing device such as a bead mill or a ball mill to obtain a ceramic slurry composition having a certain viscosity after defoaming. This slurry composition is cast onto a support surface such as a release-treated polyethylene terephthalate film or a SUS plate using a doctor blade, reverse roll coater, etc., and the volatile matter such as the solvent is distilled off by heating, etc., and then peeled off from the support to obtain a ceramic green sheet. Next, a conductive paste that will become the internal electrodes is applied to the obtained ceramic green sheets by screen printing, and multiple sheets are alternately stacked and heated and pressed to produce a laminate. After that, a process to thermally decompose and remove the binder resin components and the like contained in the laminate, that is, a so-called degreasing process, is performed, and external electrodes are sintered onto the end faces of the ceramic sintered body obtained by firing to obtain a multilayer ceramic capacitor.
[0003] For example, Patent Document 1 describes a polyvinyl acetal resin suitable as a ceramic binder, which has a specified degree of polymerization, vinyl ester unit content, and degree of acetalization, and in which the molar ratio of the portion acetalized with acetaldehyde to the portion acetalized with butylaldehyde is within a specified range. Furthermore, Patent Document 2 describes a polyvinyl acetal resin having a specific degree of polymerization, a vinyl ester unit content, and a degree of acetalization, and having specific structural units. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2011-236304 A [Patent Document 2] International Publication No. 2012 / 023517 Summary of the Invention [Problem to be solved by the invention]
[0005] Polyvinyl acetal resin is widely used as a binder for ceramic slurries for multilayer ceramic capacitors because of its good solubility in mixed solvents of ethanol and toluene. However, toluene is subject to environmental restrictions due to its harmfulness, and has a higher boiling point than ethanol, requiring more energy to dry the solvent. Therefore, there is a demand for binders that have good solubility in solvents with a high ethanol content. On the other hand, there is also the problem of sheet attack, which occurs when the binder in the dielectric layer dissolves into the electrode layer.
[0006] An object of the present invention is to provide a polyvinyl acetal resin that exhibits little change in viscosity and has excellent sheet attack resistance even when a solvent with a high proportion of ethanol is used, and to provide a slurry for a ceramic green sheet, a ceramic green sheet, and a multilayer ceramic capacitor each using the polyvinyl acetal resin. [Means for solving the problem]
[0007] The present disclosure 1 relates to a polymer having a molecular weight distribution difference of 0.5 or less calculated from the following formula (1) using the weight average molecular weight Mw(THF) and number average molecular weight Mn(THF) obtained by using THF as a mobile phase, and the weight average molecular weight Mw(NMP) and number average molecular weight Mn(NMP) obtained by using NMP as a mobile phase in a GPC measurement using a differential refractive index detector, and 13 The polyvinyl acetal resin has a ratio of the peak integral value of the methylene C atom shown in (a)' of the diad represented by the following formula (a) to the sum of the peak integral values of the methylene C atoms shown in (b)' and (c)' of the diad represented by the following formula (b) and formula (c), which is obtained by C-NMR (nuclear magnetic resonance) measurement, of 0.29 to 0.37. [Mw(THF) / Mn(THF)]-[Mw(NMP) / Mn(NMP)] (1) [ka] In formula (b) and formula (c), R is each independently a hydrogen atom or a hydrocarbon group having 1 to 20 carbon atoms. Disclosure 2 is the polyvinyl acetal resin according to Disclosure 1, in which the amount of hydroxyl groups is 28 mol % or more and 35 mol % or less. Disclosure 3 is the polyvinyl acetal resin according to Disclosure 1 or 2, which has a weight average molecular weight Mw(THF) of 200,000 or more and 500,000 or less. Disclosure 4 is the polyvinyl acetal resin according to Disclosure 1 or 2, which has a weight average molecular weight Mw(NMP) of 270,000 or more. The present disclosure 5 is a slurry for a ceramic green sheet, which contains the polyvinyl acetal resin according to the present disclosure 1 or 2, an organic solvent, and ceramic powder. The sixth aspect of the present disclosure is a ceramic green sheet obtained by using the slurry for the ceramic green sheet according to the fifth aspect of the present disclosure. The seventh aspect of the present disclosure is a multilayer ceramic capacitor obtained by using the ceramic green sheet according to the sixth aspect of the present disclosure. The present invention will be described in detail below.
[0008] As a result of intensive research, the present inventors have found that the weight average molecular weight and the number average molecular weight measured by changing the solvent satisfy a predetermined relationship, and 13 The inventors have found that a polyvinyl acetal resin in which the ratio of the peak integral value of the methylene C atom shown in (a)' of the diad represented by the above formula (a) to the sum of the peak integral values of the methylene C atoms shown in (b)' and (c)' of the diad represented by the above formula (b) and formula (c) is within a predetermined range (the ratio of the peak integral value of a diad consisting of two chains of constitutional units having a hydroxyl group) as measured by C-NMR has little change in viscosity and excellent sheet attack resistance even when a solvent with a high ratio of ethanol is used, and can be used to fabricate a multilayer ceramic capacitor with excellent reliability, thereby completing the present invention.
[0009] The polyvinyl acetal resin of the present invention has a molecular weight distribution difference of 0.5 or less, calculated from the following formula (1) using the weight average molecular weight Mw(THF) and number average molecular weight Mn(THF) obtained by using THF as a mobile phase, and the weight average molecular weight Mw(NMP) and number average molecular weight Mn(NMP) obtained by using NMP as a mobile phase. [Mw(THF) / Mn(THF)]-[Mw(NMP) / Mn(NMP)] (1) By setting the content within the above range, even when a solvent with a high proportion of ethanol is used, the viscosity change can be small. The molecular weight distribution difference is preferably 0.48 or less, more preferably 0.45 or less, and is preferably 0.001 or more, more preferably 0.01 or more. In the present invention, the difference in molecular weight distribution is an indicator of a small amount of hydrogen bonds. The molecular weight distribution difference can be calculated by measuring the weight average molecular weight Mw(THF) and the number average molecular weight Mn(THF) by gel permeation chromatography (GPC) measurement using tetrahydrofuran as the mobile phase and a differential refractive index detector as the detector, and then measuring the weight average molecular weight Mw(NMP) and the number average molecular weight Mn(NMP) by GPC measurement using N-methylpyrrolidone as the mobile phase and a differential refractive index detector as the detector, and calculating [Mw(THF) / Mn(THF)]-[Mw(NMP) / Mn(NMP)].
[0010] The z-average molecular weight Mz(THF) of the polyvinyl acetal resin of the present invention is preferably 300,000 or more and 2,000,000 or less. By setting it within the above range, the sheet attack resistance of the obtained ceramic green sheet can be maintained. The above Mz(THF) is more preferably 400,000 or more and more preferably 1,200,000 or less.
[0011] The z-average molecular weight Mz(NMP) of the polyvinyl acetal resin of the present invention is preferably 300,000 or more and 1,000,000 or less. By setting it within the above range, the sheet attack resistance of the obtained ceramic green sheet can be maintained. The above Mz(NMP) is more preferably 400,000 or more, and more preferably 600,000 or less.
[0012] The weight average molecular weight Mw(THF) of the polyvinyl acetal resin of the present invention is preferably 200,000 or more and 500,000 or less. By setting it within the above range, the elongation of the obtained ceramic green sheet can be maintained. The above Mw(THF) is more preferably 220,000 or more and more preferably 400,000 or less.
[0013] The weight average molecular weight Mw(NMP) of the polyvinyl acetal resin of the present invention is preferably 270,000 or more and 400,000 or less. By setting it within the above range, the elongation of the obtained ceramic green sheet can be maintained. The above Mw(NMP) is more preferably 275,000 or more and more preferably 300,000 or less.
[0014] The number average molecular weight Mn(THF) of the polyvinyl acetal resin of the present invention is preferably 50,000 or more and 200,000 or less. By setting it within the above range, the strength of the obtained ceramic green sheet can be maintained. The above Mw(THF) is more preferably 75,000 or more and more preferably 200,000 or less.
[0015] The number average molecular weight Mn(NMP) of the polyvinyl acetal resin of the present invention is preferably 50,000 or more and 200,000 or less. By setting it within the above range, the strength of the obtained ceramic green sheet can be maintained. The above Mw(NMP) is more preferably 75,000 or more and more preferably 200,000 or less.
[0016] The molecular weight distribution difference can be adjusted, for example, by changing the average degree of polymerization and degree of saponification of the raw material polyvinyl alcohol resin, and the temperature and time conditions of the acetalization reaction, and by appropriately setting the amount of acetal groups, hydroxyl groups, acetyl groups, etc. of the polyvinyl acetal resin. In particular, the molecular weight distribution difference can be adjusted by changing the aldehyde introduction temperature, number of introductions, introduction interval, introduction amount ratio, reaction temperature, reaction time, temperature rise time, temperature rise rate, holding (aging) temperature, and holding (aging) time during the acetalization reaction described below, and in particular, it is possible to adjust by changing the aldehyde introduction temperature, number of introductions, introduction interval, introduction amount ratio, holding (aging) temperature, and holding (aging) time.
[0017] The polyvinyl acetal resin of the present invention is 13The ratio of the peak integral value of a diad consisting of two consecutive sequences of structural units having a hydroxyl group, as measured by C-NMR, is 0.29 to 0.37. By setting it in the above range, sheet attack resistance can be improved. The ratio of the peak integral value of the diad consisting of two chains of the structural unit having a hydroxyl group has a preferable lower limit of 0.30, a more preferable lower limit of 0.31, a preferable upper limit of 0.365, and a more preferable upper limit of 0.36. If it is equal to or more than the lower limit, the hydrogen bonding property by the hydroxyl group is improved, and the ceramic green sheet produced using the polyvinyl acetal resin of the present invention can have a low solubility in organic solvents, resulting in good sheet attack resistance, whereas if it is equal to or less than the upper limit, the solubility of the polyvinyl acetal resin in organic solvents is not too low, resulting in good handleability in solution preparation and the like.
[0018] The ratio of the peak integral value of the diad, which is a chain consisting of structural units having two hydroxyl groups, is The ratio of the sum of the peak integral values of the methylene C atoms shown in (a)' of the diad represented by the following formula (a) to the sum of the peak integral values of the methylene C atoms shown in (b)' and (c)' of the diad represented by the following formula (b) and the following formula (c), 13 It can be measured by C-NMR.
[0019] 13 Obtained by C-NMR (nuclear magnetic resonance) measurement 13 In the C-NMR spectrum, the sum of the peak integral values of the methylene C atoms shown in (b)' and (c)' of the diads represented by the following formulas (b) and (c) can be calculated by the sum of these, that is, [I(b)'+I(c)'], where I(b)' is the peak integral value to which the methylene C atom shown in (b)' of the diad represented by the following formula (b) belongs, and I(c)' is the peak integral value to which the methylene C atom shown in (c)' of the diad represented by the following formula (c) belongs.
[0020] [ka] In formula (b) and formula (c), R is each independently a hydrogen atom or a hydrocarbon group having 1 to 20 carbon atoms.
[0021] 13 Obtained by C-NMR (nuclear magnetic resonance) measurement 13 In the C-NMR spectrum, the peak integral value of the methylene C atom shown in (a)' of the diad represented by the above formula (a) can be determined from the peak integral value [I(a)'] to which the methylene C atom shown in (a)' of the diad represented by the above formula (a) belongs.
[0022] 13 In the C-NMR spectrum, the above I(a)' is the peak integral value in the interval from 44.6 to 46.0 ppm, and the above I(b)'+I(c)' is the peak integral value in the interval from 42.9 to 44.6 ppm.
[0023] Regarding the polyvinyl acetal resin of the present invention, 13 Obtained by C-NMR (nuclear magnetic resonance) measurement 13 An example of a C-NMR spectrum (partially enlarged) is shown in Figure 1. 13 The peaks (a)', (b)' and (c)' shown in the C-NMR spectrum indicate the peaks assigned to the methylene C atoms shown in (a)', (b)' and (c)' of the diads represented by the above formulas (a), (b) and (c), respectively.
[0024] The ratio of the peak integral value of the diad consisting of two chains of structural units having a hydroxyl group can be adjusted, for example, by changing the average degree of polymerization and degree of saponification of the raw material polyvinyl alcohol resin, and the temperature and time conditions of the acetalization reaction, and by appropriately setting the amount of acetal groups, the amount of hydroxyl groups, the amount of acetyl groups, etc. of the polyvinyl acetal resin. In particular, the ratio of the peak integral value of the diad consisting of two chains of structural units having a hydroxyl group can be adjusted by changing the aldehyde introduction temperature, number of introductions, introduction interval, reaction temperature, reaction time, temperature rise time, temperature rise rate, holding (aging) temperature, and holding (aging) time during the acetalization reaction described below, and in particular, it can be adjusted by changing the aldehyde introduction temperature, holding (aging) temperature, and holding (aging) time.
[0025] The polyvinyl acetal resin of the present invention preferably has a solution viscosity of 60 mPa s or more and 600 mPa s or less, when a 5% by mass solution of the polyvinyl acetal resin in a 1:1 mixed solvent of ethanol and toluene is measured using a B-type viscometer at a solution temperature of 20°C. In order to improve the tensile strength, the viscosity is more preferably 65 mPa s or more, and even more preferably 70 mPa s or more. In order to improve the viscosity stability of the ceramic slurry composition, the viscosity is more preferably 300 mPa s or less, and even more preferably 150 mPa s or less. The above-mentioned B-type viscometer may be, for example, a TVB-10 viscometer manufactured by Toki Sangyo Co., Ltd. In addition, the rotor and rotation speed during viscosity measurement are preferably adjusted appropriately depending on the solution viscosity, and for example, it is preferable to measure using SPINDLE No. M1 to M4 at a rotation speed in the range of 0.3 to 100 rpm.
[0026] The viscosity can be adjusted, for example, by changing the average degree of polymerization and degree of saponification of the raw material polyvinyl alcohol resin, and the temperature and time conditions of the acetalization reaction, and by appropriately setting the amount of acetal groups, hydroxyl groups, acetyl groups, etc. of the polyvinyl acetal resin.
[0027] The polyvinyl acetal resin of the present invention preferably has a structural unit having an acetal group represented by the following formula (3), a structural unit having a hydroxyl group represented by the following formula (4), and a structural unit having an acetyl group represented by the following formula (5).
[0028] [ka]
[0029] In the above formula (3), R 1 represents a hydrogen atom or an alkyl group having 1 to 20 carbon atoms.
[0030] In the above formula (3), R 1 When is an alkyl group having 1 to 20 carbon atoms, examples of the alkyl group include a methyl group, an ethyl group, an n-propyl group, an isopropyl group, an n-butyl group, an isobutyl group, a sec-butyl group, a tert-butyl group, a pentyl group, a hexyl group, a heptyl group, a 2-ethylhexyl group, an octyl group, a nonyl group, a decyl group, an undecyl group, a dodecyl group, a tridecyl group, a tetradecyl group, a pentadecyl group, an octadecyl group, etc. Among these, a methyl group and an n-propyl group are preferable.
[0031] In the polyvinyl acetal resin of the present invention, the content of the structural unit having the acetal group represented by the above formula (3) (hereinafter also referred to as the "acetal group amount") is preferably 50 mol % in lower limit and 83 mol % in upper limit. When the amount of acetal groups is 50 mol % or more, the solubility in organic solvents can be improved, and when the amount of acetal groups is 83 mol % or less, the polyvinyl acetal resin can have excellent tensile strength. The acetal group amount is more preferably 55 mol % in lower limit and 80 mol % in upper limit, that is, the acetal group amount is preferably 50 to 83 mol %, and more preferably 55 to 80 mol %. The amount of acetal groups is, for example, 1 It can be measured by H-NMR. Regarding the method for calculating the amount of acetal groups, since the acetal groups of polyvinyl acetal resin are obtained by acetalizing two hydroxyl groups of polyvinyl alcohol, the method of counting the two acetalized hydroxyl groups is used.
[0032] In the polyvinyl acetal resin of the present invention, the content of the structural unit having a hydroxyl group represented by the above general formula (4) (hereinafter also referred to as the "hydroxyl group amount") is preferably 28 mol % in lower limit and 35 mol % in upper limit. If the amount of hydroxyl groups is 28 mol % or more, the polyvinyl acetal resin can have high toughness, and if the amount of hydroxyl groups is 35 mol % or less, the solubility in organic solvents can be sufficiently improved. The lower limit of the hydroxyl group amount is more preferably 29 mol % and the upper limit is more preferably 34 mol %. That is, the hydroxyl group amount is preferably 28 to 35 mol %, and more preferably 29 to 34 mol %. The amount of hydroxyl groups is, for example, 1 It can be measured by H-NMR.
[0033] In the polyvinyl acetal resin of the present invention, the content of the structural unit having an acetyl group represented by the above general formula (5) (hereinafter also referred to as the "acetyl group amount") is preferably 0.1 mol % in lower limit and 22.0 mol % in upper limit. When the amount of acetyl groups is 0.1 mol% or more, the increase in viscosity of the slurry for ceramic green sheets due to intramolecular and intermolecular hydrogen bonds of hydroxyl groups in the polyvinyl acetal resin can be suppressed.When the amount of acetyl groups is 22.0 mol% or less, the flexibility of the polyvinyl acetal resin is not excessively increased, and the handleability can be improved. The acetyl group amount has a more preferable lower limit of 0.5 mol % and a more preferable upper limit of 15.0 mol %. That is, the acetyl group amount is preferably 0.1 to 22.0 mol %, and more preferably 0.5 to 15 mol %. The amount of acetyl groups is, for example, 1 It can be measured by H-NMR.
[0034] In the polyvinyl acetal resin of the present invention, from the viewpoint of maintaining mechanical strength when a thin film ceramic green sheet is produced, the average polymerization degree has a preferable lower limit of 500, more preferably 600, and from the viewpoint of solubility in organic solvents and dissolution viscosity, the average polymerization degree is preferably 10,000, more preferably 9,000. That is, the average polymerization degree is preferably 500 to 10,000, more preferably 600 to 9,000. The average degree of polymerization of the polyvinyl acetal resin is the same as that of the raw material polyvinyl alcohol, and can be measured in accordance with JIS K 6726.
[0035] The polyvinyl acetal resin of the present invention can usually be produced by acetalizing a polyvinyl alcohol resin.
[0036] As the polyvinyl alcohol resin, for example, a conventionally known polyvinyl alcohol resin such as a resin produced by saponifying a polyvinyl acetate resin with an alkali, an acid, aqueous ammonia or the like can be used. The polyvinyl alcohol resin may be fully saponified, but it does not need to be fully saponified as long as there is at least one unit having two consecutive hydroxyl groups at the meso and racemo positions at at least one position in the main chain, and may be a partially saponified polyvinyl alcohol resin. In addition, as the polyvinyl alcohol resin, a copolymer of vinyl alcohol and a monomer copolymerizable with vinyl alcohol, such as an ethylene-vinyl alcohol copolymer resin or a partially saponified ethylene-vinyl alcohol copolymer resin, may also be used. The polyvinyl acetate resin may be, for example, an ethylene-vinyl acetate copolymer.
[0037] The polyvinyl alcohol resin preferably has a degree of saponification of 75 mol % or more. The saponification degree is preferably 76 mol % or more and 99.4 mol % or less, and more preferably 78 mol % or more and 98 mol % or less. That is, the saponification degree is preferably 76 to 99.4 mol %, and more preferably 78 to 98 mol %. By using the polyvinyl alcohol resin, the Mz can be set within a predetermined range.
[0038] The above acetalization is preferably carried out in a water solvent, in a mixed solvent of water and an organic solvent compatible with water, or in an organic solvent. As the organic solvent compatible with water, for example, an alcohol-based organic solvent can be used. Examples of the organic solvent include alcohol-based organic solvents, aromatic organic solvents, aliphatic ester-based solvents, ketone-based solvents, lower paraffin-based solvents, ether-based solvents, amide-based solvents, and amine-based solvents. Examples of the alcohol-based organic solvent include methanol, ethanol, n-propanol, isopropanol, n-butanol, and tert-butanol. Examples of the aromatic organic solvent include xylene, toluene, ethylbenzene, and methyl benzoate. Examples of the aliphatic ester solvent include methyl acetate, ethyl acetate, butyl acetate, methyl propionate, ethyl propionate, methyl butyrate, ethyl butyrate, methyl acetoacetate, and ethyl acetoacetate. Examples of the ketone solvent include acetone, methyl ethyl ketone, methyl isobutyl ketone, cyclohexanone, methylcyclohexanone, benzophenone, and acetophenone. Examples of the lower paraffin solvent include hexane, pentane, octane, cyclohexane, and decane. Examples of the ether solvent include diethyl ether, tetrahydrofuran, ethylene glycol dimethyl ether, ethylene glycol diethyl ether, and propylene glycol diethyl ether. Examples of the amide solvent include N,N-dimethylformamide, N,N-dimethylacetamide, N-methylpyrrolidone, and acetanilide. Examples of the amine solvent include ammonia, trimethylamine, triethylamine, n-butylamine, di-n-butylamine, tri-n-butylamine, aniline, N-methylaniline, N,N-dimethylaniline, and pyridine. These solvents may be used alone or in combination of two or more. Among these, ethanol, n-propanol, isopropanol, and tetrahydrofuran are particularly preferred from the viewpoints of solubility in the resin and ease of purification.
[0039] The acetalization is preferably carried out in the presence of an acid catalyst. The acid catalyst is not particularly limited, and examples thereof include mineral acids such as sulfuric acid, hydrochloric acid, nitric acid, and phosphoric acid, carboxylic acids such as formic acid, acetic acid, and propionic acid, and sulfonic acids such as methanesulfonic acid, ethanesulfonic acid, benzenesulfonic acid, and paratoluenesulfonic acid. These acid catalysts may be used alone or in combination of two or more compounds. Among them, hydrochloric acid, nitric acid, and sulfuric acid are preferred, and hydrochloric acid is particularly preferred.
[0040] The aldehyde used in the acetalization reaction may be an aldehyde having a chain aliphatic group, a cyclic aliphatic group, or an aromatic group having 1 to 10 carbon atoms. Any known aldehyde may be used as the aldehyde. The aldehyde used in the acetalization reaction is not particularly limited, and may be, for example, an aliphatic aldehyde, an aromatic aldehyde, or the like. Examples of the aliphatic aldehyde include formaldehyde, acetaldehyde, propionaldehyde, n-butyraldehyde, isobutyraldehyde, n-valeraldehyde, n-hexylaldehyde, 2-ethylbutyraldehyde, 2-ethylhexylaldehyde, n-heptylaldehyde, n-octylaldehyde, n-nonylaldehyde, n-decylaldehyde, and amylaldehyde. Examples of the aromatic aldehyde include benzaldehyde, cinnamaldehyde, 2-methylbenzaldehyde, 3-methylbenzaldehyde, 4-methylbenzaldehyde, p-hydroxybenzaldehyde, m-hydroxybenzaldehyde, phenylacetaldehyde, and β-phenylpropionaldehyde. These aldehydes may be used alone or in combination of two or more. Among them, preferred aldehydes are formaldehyde, acetaldehyde, butylaldehyde, 2-ethylhexylaldehyde, and n-nonylaldehyde, which have excellent acetalization reactivity and can provide sufficient internal plasticizing effect to the resin produced, thereby imparting good flexibility. In addition, more preferred are formaldehyde, acetaldehyde, and butylaldehyde, which can provide an adhesive composition that is particularly excellent in impact resistance and adhesion to metals.
[0041] The amount of the aldehyde to be added can be appropriately set according to the amount of acetal groups in the target polyvinyl acetal resin. In particular, it is preferable to add 50 mol% or more and 95 mol% or less, more preferably 55 mol% or more and 90 mol% or less, based on 100 mol% of polyvinyl alcohol, because this allows the acetalization reaction to proceed efficiently and makes it easy to remove unreacted aldehyde.
[0042] In the acetalization, it is preferable to add the aldehyde in several portions. The number of times of addition of the aldehyde is preferably 2. The ratio of the amount of the aldehyde added in the first time to the total amount of the aldehyde added is preferably 1% or more and 50% or less, more preferably 2% or more and 40% or less, of the total amount. When the aldehyde is added in a number of portions, the temperature during the first addition is preferably 15°C or higher and 60°C or lower, and more preferably 25°C or higher and 50°C or lower. The temperature during the final addition is preferably 10°C or higher and 50°C or lower, and more preferably 20°C or higher and 40°C or lower. Furthermore, the interval between the first and last addition is preferably 5 minutes or more and 180 minutes or less, and more preferably 10 minutes or more and 120 minutes or less.
[0043] In the above acetalization, it is preferable to add the above aldehyde, carry out the reaction at a predetermined temperature (reaction step), and then raise the temperature and maintain it at the predetermined temperature (aging step). The time from the final addition to the start of temperature rise (reaction time) is preferably 10 minutes or more and 120 minutes or less, more preferably 20 minutes or more and 90 minutes or less. The temperature in the reaction step (reaction temperature) is preferably in the same range as the temperature at the final addition. The temperature rise time from the end of the reaction step to the aging step is preferably 30 minutes or more and 500 minutes or less, and more preferably 60 minutes or more and 400 minutes or less. The rate of temperature rise from the start of the temperature rise to the aging step is preferably 0.1° C. / min or more and 2° C. / min or less.
[0044] The retention time in the aging step is preferably 0.5 hours or more and 6 hours or less, and more preferably 1 hour or more and 5 hours or less. The holding temperature in the aging step is preferably 50°C or higher and 80°C or lower, and more preferably 55°C or higher and 75°C or lower. By using the above-mentioned holding time and holding temperature, the ratio of the peak integral value of the diad consisting of two consecutive chains of structural units having a hydroxyl group can be kept within a predetermined range.
[0045] By containing the polyvinyl acetal resin of the present invention and a plasticizer, a resin composition for a ceramic green sheet can be obtained. The resin composition for a ceramic green sheet may contain components such as an antioxidant, a surfactant, an ultraviolet absorber, and a defoaming agent, so long as the effects of the present invention are not adversely affected.
[0046] As a method for producing the resin composition for ceramic green sheets, for example, a plasticizer and other additives added as necessary are added to a polyvinyl acetal resin obtained by acetalizing a polyvinyl alcohol resin with an aldehyde, and then mixed to obtain a resin composition for ceramic green sheets.
[0047] The resin composition for a ceramic green sheet contains a plasticizer. By adding the plasticizer, the mechanical strength and flexibility of the resulting ceramic green sheet can be significantly improved. Examples of the plasticizer include phthalic acid diesters such as dioctyl phthalate (DOP) and dibutyl phthalate (DBP), adipic acid diesters such as dioctyl adipate, and alkylene glycol diesters such as triethylene glycol-di-2-ethylhexanoate, tetraethylene glycol-di-2-ethylhexanoate, triethylene glycol-di-2-ethylbutyrate, tetraethylene glycol-di-2-ethylbutyrate, tetraethylene glycol-di-heptanoate, and triethylene glycol-di-heptanoate.
[0048] In the resin composition for ceramic green sheets, the content of the plasticizer relative to 100 parts by weight of the polyvinyl acetal resin is preferably 7 parts by weight in lower limit, more preferably 8.5 parts by weight in lower limit, preferably 18 parts by weight in upper limit, more preferably 13.5 parts by weight in upper limit.
[0049] A slurry for ceramic green sheets can be prepared by mixing the polyvinyl acetal resin of the present invention with an organic solvent and ceramic powder.
[0050] The organic solvent is not particularly limited, and may be any solvent capable of dissolving the polyvinyl acetal resin, such as ketones, including acetone, methyl ethyl ketone, dipropyl ketone, and diisobutyl ketone. Other examples include alcohols, such as methanol, ethanol, isopropanol, and butanol, and aromatic hydrocarbons, such as toluene and xylene. Other examples include esters, such as methyl propionate, ethyl propionate, butyl propionate, methyl butanoate, ethyl butanoate, butyl butanoate, methyl pentanoate, ethyl pentanoate, butyl pentanoate, methyl hexanoate, ethyl hexanoate, butyl hexanoate, 2-ethylhexyl acetate, and 2-ethylhexyl butyrate. Other examples include methyl cellosolve, ethyl cellosolve, butyl cellosolve, terpineol, dihydroterpineol, butyl cellosolve acetate, butyl carbitol acetate, terpineol acetate, and dihydroterpineol acetate. In particular, alcohols, ketones, aromatic hydrocarbons and mixed solvents thereof are preferred in terms of coating and drying properties, with a mixed solvent of ethanol and toluene and a mixed solvent of methyl ethyl ketone and toluene being more preferred.
[0051] The content of the organic solvent in the ceramic green sheet slurry is set according to the type of polyvinyl acetal resin used and is not particularly limited, but if it is too small, it is difficult to exhibit the solubility required for kneading. Also, if it is too large, the viscosity of the ceramic green sheet slurry becomes too low, which may cause poor handling when producing a ceramic green sheet. For this reason, the content of the organic solvent is preferably 20% by weight or more and 80% by weight or less.
[0052] The ceramic powder includes powders of oxides or non-oxides of metals or non-metals used in the manufacture of ceramics. The composition of these powders may be a single composition, a compound state, or a mixture. The constituent elements of the metal oxide or non-oxide may be a single element or a plurality of elements, both as cations and anions, and may further include additives added to improve the properties of the oxide or non-oxide. Specific examples of the oxides or non-oxides include oxides, carbides, nitrides, borides, and sulfides of Li, K, Mg, B, Al, Si, Cu, Ca, Sr, Ba, Zn, Cd, Ga, In, Y, lanthanides, actinides, Ti, Zr, Hf, Bi, V, Nb, Ta, W, Mn, Fe, Co, Ni, etc. In addition, oxide powders containing multiple metal elements, usually called double oxides, can be classified based on their crystal structure as having a perovskite structure, such as NaNbO 3 , SrZrO 3 , PbZrO 3 , SrTiO 3 , BaZrO 3 , PbTiO 3 , BaTiO 3 As examples of materials with a spinel structure, MgAl 2 O 4 , ZnAl 2 O 4 , CoAl 2 O 4 , NiAl 2 O4, MgFe 2 O 4 Examples of materials with an ilmenite structure include MgTiO 3 , MnTiO 3 , FeTiO 3 The garnet-type structure is GdGa 5 O 12 , Y 6 Fe 5 O 12 Among these, the modified polyvinyl acetal resin of the present invention is BaTiO 3 It shows high properties when mixed with ceramic green sheets containing powder.
[0053] The average particle size of the ceramic powder is not particularly limited, but for example, for producing a thin ceramic green sheet (thickness 5 μm or less), it is preferably 0.5 μm or less.
[0054] The above-mentioned slurry for ceramic green sheets may contain other resins such as polyvinyl acetal resins other than the polyvinyl acetal resin of the present invention, acrylic resins, ethyl cellulose, etc., within the range that does not impair the effects of the present invention. In such a case, the content of the polyvinyl acetal resin of the present invention relative to the total binder resins is preferably 50% by weight or more.
[0055] The above-mentioned slurry for the ceramic green sheet may contain, as necessary, a dispersant, an antioxidant, an ultraviolet absorber, a surfactant, a filler, etc., and in some cases, a small amount of other resin such as an acrylic resin or a urethane resin may be added.
[0056] The method for producing the slurry for the ceramic green sheet is not particularly limited, and examples thereof include a method in which the polyvinyl acetal resin of the present invention, an organic solvent, a ceramic powder, and various additives added as necessary are mixed using various mixers such as a ball mill, a blender mill, and a three-roll mill.
[0057] After the slurry for the ceramic green sheet is applied, the slurry is heated and dried to obtain a ceramic green sheet. The ceramic green sheets can be used to manufacture ceramic electronic components. For example, the ceramic electronic components can be manufactured by carrying out a step of applying a paste for electrode layers to the surfaces of the ceramic green sheets, and a step of stacking the ceramic green sheets on which the electrode layers have been formed, and heat-pressing the stack to obtain a laminate, followed by degreasing and firing the laminate.
[0058] The method for applying the slurry for the ceramic green sheet is not particularly limited, and examples thereof include a method using a roll coater, a die coater, a curtain coater, etc. As for other specific methods, conventionally known methods can be used.
[0059] The ceramic electronic components are not particularly limited, and examples thereof include multilayer ceramic capacitors, multilayer ceramic inductors, capacitors, piezoelectric actuators, multilayer varistors, multilayer thermistors, EMI filters, aluminum nitride multilayer substrates, alumina multilayer substrates, etc. Such multilayer ceramic capacitors also constitute the present invention.
[0060] The method for producing a ceramic electronic component includes a step of applying a paste for electrode layers to the surfaces of the ceramic green sheets. The electrode layer paste can be obtained by dissolving, for example, polyvinyl acetal resin, ethyl cellulose, acrylic resin, etc. as a binder resin in an organic solvent and dispersing conductive powder, etc. These resins may be used alone or in combination of two or more. The electrode layer paste containing polyvinyl acetal resin is preferred because it exhibits excellent adhesion to the ceramic green sheet in the heat-pressing step.
[0061] In the method for producing a ceramic electronic component, the above-mentioned ceramic green sheets having electrode layers formed thereon are produced, and then similarly produced ceramic green sheets having electrode layers formed thereon are stacked and heated and pressed to obtain a laminate, which is then degreased and fired, thereby obtaining a multilayer ceramic electronic component in which problems such as sheet attack and cracks are solved. The above-mentioned heat-pressure bonding step and the steps of degreasing and firing the laminate are not particularly limited, and conventionally known methods can be used. Effect of the Invention
[0062] According to the present invention, it is possible to provide a polyvinyl acetal resin which exhibits little change in viscosity and excellent sheet attack resistance even when a solvent having a high proportion of ethanol is used, as well as a slurry for a ceramic green sheet, a ceramic green sheet, and a multilayer ceramic capacitor which use the polyvinyl acetal resin. [Brief description of the drawings]
[0063] [Figure 1] FIG. 2 is a partially enlarged view showing an example of a 13C-NMR (nuclear magnetic resonance) spectrum obtained by 13C-NMR measurement of the polyvinyl acetal resin of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0064] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples.
[0065] Example 1 3000g of pure water was added to 300g of polyvinyl alcohol resin (average polymerization degree 1700, saponification degree 99.1 mol%), and the mixture was stirred at 90°C for about 2 hours to dissolve. The solution was cooled to 30°C, and 220g of hydrochloric acid with a concentration of 35% by weight and 30g of n-butylaldehyde were added to the solution (first addition). The solution was then cooled to 20°C, and 30 minutes after the first addition, 130g of n-butylaldehyde was further added (second addition). After that, the mixture was held for 0.5 hours to carry out the acetalization reaction, and then the temperature was increased at a rate of 0.2°C / min (heating time: 150 minutes) and the mixture was held at 55°C for 3 hours (aging process) to complete the reaction. The mixture was then neutralized, washed with water and dried in the usual manner to obtain a white powder of polyvinyl acetal resin.
[0066] Example 2 3000g of pure water was added to 300g of polyvinyl alcohol resin (average polymerization degree 1700, saponification degree 99.0 mol%), and the mixture was stirred at 90°C for about 2 hours to dissolve. The solution was cooled to 30°C, and 220g of hydrochloric acid with a concentration of 35% by weight and 40g of n-butylaldehyde were added to the solution (first addition). The solution was then cooled to 20°C, and 30 minutes after the first addition, 120g of n-butylaldehyde was further added (second addition). After that, the mixture was held for 0.5 hours to carry out the acetalization reaction, and then the temperature was increased at a rate of 0.2°C / min (heating time: 150 minutes) and the mixture was held at 55°C for 3 hours (aging process) to complete the reaction. The mixture was then neutralized, washed with water and dried in the usual manner to obtain a white powder of polyvinyl acetal resin.
[0067] Example 3 3000g of pure water was added to 300g of polyvinyl alcohol resin (average polymerization degree 1700, saponification degree 99.2 mol%), and the mixture was stirred at 90°C for about 2 hours to dissolve. The solution was cooled to 35°C, and 220g of hydrochloric acid with a concentration of 35% by weight and 10g of n-butylaldehyde were added to the solution (first addition). The solution was then cooled to 30°C, and 15 minutes after the first addition, 150g of n-butylaldehyde was further added (second addition). After that, the mixture was held for 0.5 hours to carry out the acetalization reaction, and then the temperature was increased at a rate of 0.2°C / min (heating time: 100 minutes) and the mixture was held at 55°C for 3 hours (aging process) to complete the reaction. The mixture was then neutralized, washed with water and dried in the usual manner to obtain a white powder of polyvinyl acetal resin.
[0068] Example 4 3000g of pure water was added to 300g of polyvinyl alcohol resin (average polymerization degree 1700, saponification degree 99.2 mol%), and the mixture was stirred at 90°C for about 2 hours to dissolve. The solution was cooled to 30°C, and 220g of hydrochloric acid with a concentration of 35% by weight and 30g of n-butylaldehyde were added thereto (first addition). The solution was then cooled to 20°C, and 30 minutes after the first addition, 130g of n-butylaldehyde was further added thereto (second addition). After that, the mixture was held for 0.5 hours to carry out the acetalization reaction, and then the temperature was increased at a rate of 0.2°C / min (heating time: 180 minutes) and the mixture was held at 60°C for 3 hours (aging process) to complete the reaction. The mixture was then neutralized, washed with water and dried in the usual manner to obtain a white powder of polyvinyl acetal resin.
[0069] Example 5 3000g of pure water was added to 300g of polyvinyl alcohol resin (average polymerization degree 1700, saponification degree 99.2 mol%), and the mixture was stirred at 90°C for about 2 hours to dissolve. The solution was cooled to 35°C, and 220g of hydrochloric acid with a concentration of 35% by weight and 10g of n-butylaldehyde were added to the solution (first addition). The solution was then cooled to 30°C, and 15 minutes after the first addition, 150g of n-butylaldehyde was further added (second addition). After that, the mixture was held for 0.5 hours to carry out the acetalization reaction, and then the temperature was increased at a rate of 0.2°C / min (heating time: 120 minutes) and the mixture was held at 60°C for 3 hours (aging process) to complete the reaction. The mixture was then neutralized, washed with water and dried in the usual manner to obtain a white powder of polyvinyl acetal resin.
[0070] Example 6 3000g of pure water was added to 300g of polyvinyl alcohol resin (average polymerization degree 1700, saponification degree 99.1 mol%), and the mixture was stirred at 90°C for about 2 hours to dissolve. The solution was cooled to 45°C, and 220g of hydrochloric acid with a concentration of 35% by weight and 10g of n-butylaldehyde were added thereto (first addition). The solution was then cooled to 40°C, and 10 minutes after the first addition, 150g of n-butylaldehyde was further added thereto (second addition). After that, the mixture was held for 0.5 hours to carry out the acetalization reaction, and then the temperature was increased at a rate of 0.2°C / min (heating time: 90 minutes) and the mixture was held at 55°C for 3 hours (aging process) to complete the reaction. The mixture was then neutralized, washed with water and dried in the usual manner to obtain a white powder of polyvinyl acetal resin.
[0071] Example 7 3000g of pure water was added to 300g of polyvinyl alcohol resin (average polymerization degree 1700, saponification degree 99.2 mol%), and the mixture was stirred at 90°C for about 2 hours to dissolve. The solution was cooled to 35°C, and 220g of hydrochloric acid with a concentration of 35% by weight and 10g of n-butylaldehyde were added to the solution (first addition). The solution was then cooled to 30°C, and 15 minutes after the first addition, 150g of n-butylaldehyde was further added (second addition). After that, the mixture was held for 0.5 hours to carry out the acetalization reaction, and then the temperature was increased at a rate of 0.2°C / min (heating time: 200 minutes) and the mixture was held at 70°C for 0.5 hours (aging process) to complete the reaction. The mixture was then neutralized, washed with water and dried in the usual manner to obtain a white powder of polyvinyl acetal resin.
[0072] Comparative Example 1 3000 g of polyvinyl alcohol resin (average polymerization degree 1700, saponification degree 99.4 mol%) was added to 300 g of pure water and dissolved by stirring for about 2 hours at 90° C. The solution was cooled to 20° C., and 220 g of hydrochloric acid with a concentration of 35% by weight and 160 g of n-butyl aldehyde were added thereto. After that, the mixture was held for 0.5 hours to carry out the acetalization reaction, and then the temperature was increased at a rate of 0.2°C / min (heating time: 120 minutes) and the mixture was held at 55°C for 3 hours (aging process) to complete the reaction. The mixture was then neutralized, washed with water and dried in the usual manner to obtain a white powder of polyvinyl acetal resin.
[0073] Comparative Example 2 3000 g of polyvinyl alcohol resin (average polymerization degree 1700, saponification degree 99.4 mol%) was added to 300 g of pure water and dissolved by stirring for about 2 hours at 90° C. The solution was cooled to 20° C., and 220 g of hydrochloric acid with a concentration of 35% by weight and 160 g of n-butyl aldehyde were added thereto. After that, the mixture was held for 0.5 hours to carry out the acetalization reaction, and then the temperature was increased at a rate of 0.2°C / min (heating time: 50 minutes) and the mixture was held at 30°C for 3 hours (aging process) to complete the reaction. The mixture was then neutralized, washed with water and dried in the usual manner to obtain a white powder of polyvinyl acetal resin.
[0074] Comparative Example 3 3000g of pure water was added to 300g of polyvinyl alcohol resin (average polymerization degree 1700, saponification degree 99.1 mol%), and the mixture was stirred at 90°C for about 2 hours to dissolve. The solution was cooled to 30°C, and 220g of hydrochloric acid with a concentration of 35% by weight and 130g of n-butylaldehyde were added to the solution (first addition). The solution was then cooled to 20°C, and 30 minutes after the first addition, 30g of n-butylaldehyde was further added (second addition). After that, the mixture was held for 0.5 hours to carry out the acetalization reaction, and then the temperature was increased at a rate of 0.2°C / min (heating time: 50 minutes) and the mixture was held at 30°C for 3 hours (aging process) to complete the reaction. The mixture was then neutralized, washed with water and dried in the usual manner to obtain a white powder of polyvinyl acetal resin.
[0075] Comparative Example 4 3000g of pure water was added to 300g of polyvinyl alcohol resin (average polymerization degree 1700, saponification degree 99.2 mol%), and the mixture was stirred at 90°C for about 2 hours to dissolve. The solution was cooled to 30°C, and 220g of hydrochloric acid with a concentration of 35% by weight and 130g of n-butylaldehyde were added to the solution (first addition). The solution was then cooled to 20°C, and 30 minutes after the first addition, 30g of n-butylaldehyde was further added (second addition). After that, the mixture was held for 0.5 hours to carry out the acetalization reaction, and then the temperature was increased at a rate of 0.2°C / min (heating time: 200 minutes) and the mixture was held at 60°C for 5 hours (aging process) to complete the reaction. The mixture was then neutralized, washed with water and dried in the usual manner to obtain a white powder of polyvinyl acetal resin.
[0076] (evaluation) The polyvinyl acetal resins obtained in the examples and comparative examples were evaluated as follows. The results are shown in Table 1.
[0077] (1) Evaluation of polyvinyl acetal resin (1-1) Amount of acetal groups, hydroxyl groups, and acetyl groups The polyvinyl acetal resin thus obtained was analyzed using an AV400 spectrometer (manufactured by Bruker Corporation). 1 H-NMR measurement was carried out, and the amounts of acetal groups, hydroxyl groups, and acetyl groups were calculated. The obtained polyvinyl acetal resin was dissolved in DMSO-D 6 The solution was dissolved in water to a concentration of 1.6% by weight to prepare a measurement solution. 1 H-NMR measurements were carried out at 80 °C.
[0078] (1-2) Measurement of weight average molecular weight and number average molecular weight The obtained polyvinyl acetal resin was dissolved in tetrahydrofuran (THF) at a concentration of 0.2% by weight, passed through a PTFE filter with a pore size of 0.45 μm, and measured at a flow rate of 0.35 mL / min using a GPC apparatus HLC-8420 (manufactured by Tosoh Corporation), THF as the mobile phase, a differential refractive index detector Bryce type double pass (manufactured by Tosoh Corporation) as the detector, and a column TSKgelSuperHZM-H (manufactured by Tosoh Corporation). The obtained measurement results were calibrated using a molecular weight calibration curve prepared with a monodisperse polystyrene standard sample, and the number average molecular weight Mn (THF) and weight average molecular weight Mw (THF) were obtained. Similarly, the obtained polyvinyl acetal resin was dissolved in N-methylpyrrolidone (NMP) at a concentration of 0.2% by weight, passed through a PTFE filter with a pore size of 0.45 μm, and measured at a flow rate of 0.5 mL / min using a GPC apparatus GPC-101 (Shodex Co., Ltd.), a mobile phase NMP, a detector RI-715 (Shodex Co., Ltd.), and a column LF-804 (Shodex Co., Ltd.). The obtained measurement results were calibrated using a molecular weight calibration curve prepared using a monodisperse polystyrene standard sample to obtain the number average molecular weight Mn (NMP) and weight average molecular weight Mw (NMP). From the obtained Mw(THF), Mn(THF), Mw(NMP) and Mn(NMP), [Mw(THF) / Mn(THF)]-[Mw(NMP) / Mn(NMP)] was calculated as the molecular weight distribution difference.
[0079] (1-3) Proportion of peak integral value of diads consisting of two consecutive chains of structural units having hydroxyl groups in polyvinyl acetal resin (proportion of di-sequence hydroxyl group structural units) The polyvinyl acetal resin thus obtained was analyzed using an AVANCE600 spectrometer and a CryoProbe (manufactured by Bruker Corporation).13 The ratio of the peak integral value of the triad unit consisting of two consecutive chains of constitutional units having hydroxyl groups in the polyvinyl acetal resin was measured by C-NMR measurement. The details of the peak integral value measurement are as described above. The obtained polyvinyl acetal resin was dissolved in DMSO-D 6 The solution was dissolved in water to a concentration of 12% by weight, and a relaxation reagent (chromium (III) acetyl acetate) was added to prepare a measurement solution. 13 C-NMR measurements were performed at 80°C in POWER Gated 1H decoupling mode.
[0080] (2) Evaluation of polyvinyl acetal resin sheet 10.0 parts by weight of the obtained polyvinyl acetal resin and 45 parts by weight of an ethanol / toluene mixed solvent (weight ratio 1:1) were added and dissolved with stirring to obtain a polyvinyl acetal resin composition. The obtained polyvinyl acetal resin composition was applied onto a release-treated PET film using a coater so that the thickness after drying would be 20 μm, and then the film was dried by heating to prepare a polyvinyl acetal resin sheet.
[0081] (2-1) Sheet attack resistance evaluation (solvent elution) The obtained polyvinyl acetal resin sheet was cut into a 1.5 cm x 10 cm square and weighed accurately. The test piece was then immersed in 10 ml of dihydroterpineol acetate at 23°C for 1 minute. The test piece was then removed and dried at 150°C for 6 hours to completely dry out the solvent. After removing from the dryer, the specimen was left at room temperature for 1 hour and then weighed. The amount of resin eluted was calculated from the change in weight before and after the test, and the elution rate was calculated from the ratio of the eluted amount to the weight of the test piece before the test, and was evaluated according to the following criteria. low It means that the sheet attack resistance is better.
[0082] A: Dissolution rate is 4.1% or less B: Dissolution rate is more than 4.1% and less than 4.7% C: Dissolution rate is more than 4.7%
[0083] (3) Viscosity change rate when ethanol ratio is changed A 5% by mass solution of a polyvinyl acetal resin dissolved in a mixed solvent of 50 parts by weight of ethanol and 50 parts by weight of toluene was measured using a Brookfield viscometer at a solution temperature of 20° C. (50% by weight ethanol viscosity). As the Brookfield viscometer, for example, a TVB-10 viscometer manufactured by Toki Sangyo Co., Ltd. can be used. The rotor and rotation speed during viscosity measurement are preferably adjusted appropriately depending on the viscosity of the solution, and for example, it is preferable to measure using SPINDLE No. M1 to M4 at a rotation speed in the range of 0.3 to 100 rpm. In addition, the viscosity (70% ethanol viscosity) was measured under the same conditions when "50 parts by weight of ethanol and 50 parts by weight of toluene" was changed to "70 parts by weight of ethanol and 30 parts by weight of toluene," and the viscosity change rate of "70% ethanol viscosity" relative to "50% ethanol viscosity" [(70% ethanol viscosity / 50% ethanol viscosity) x 100] was calculated. The obtained viscosity change rate was evaluated according to the following criteria.
[0084] A: Viscosity change rate is 104% or less B: Viscosity change rate is over 104% and less than 110% C: Viscosity change rate is 110% or more
[0085] [Table 1] [Industrial Applicability]
[0086] According to the present invention, it is possible to provide a polyvinyl acetal resin which exhibits little change in viscosity and excellent sheet attack resistance even when a solvent having a high proportion of ethanol is used, as well as a slurry for a ceramic green sheet, a ceramic green sheet, and a multilayer ceramic capacitor which use the polyvinyl acetal resin.
Claims
1. In a GPC measurement using a differential refractive index detector, the molecular weight distribution difference calculated from the following formula (1) using the weight average molecular weight Mw(THF) and number average molecular weight Mn(THF) obtained by using THF as a mobile phase and the weight average molecular weight Mw(NMP) and number average molecular weight Mn(NMP) obtained by using NMP as a mobile phase is 0.5 or less, and 13 A polyvinyl acetal resin in which the ratio of the peak integral value of the methylene C atom shown in (a)' of a diad represented by the following formula (a) to the sum of the peak integral values of the methylene C atoms shown in (b)' and (c)' of a diad represented by the following formula (b) and formula (c) is 0.29 to 0.37, as obtained by C-NMR (nuclear magnetic resonance) measurement, the amount of acetal groups is 50 mol % or more and 68.5 mol % or less, and the amount of hydroxyl groups is 28 mol % or more and 35 mol % or less. [Mw(THF) / Mn(THF)]-[Mw(NMP) / Mn(NMP)] (1) 【Chemistry 1】 In formula (b) and formula (c), R is each independently a hydrogen atom or a hydrocarbon group having 1 to 20 carbon atoms.
2. The polyvinyl acetal resin according to claim 1, having a weight average molecular weight Mw(THF) of 200,000 or more and 500,000 or less.
3. 3. The polyvinyl acetal resin according to claim 1 or 2, having a weight average molecular weight Mw(NMP) of 270,000 or more.
4. A slurry for a ceramic green sheet, comprising the polyvinyl acetal resin according to claim 1 or 2, an organic solvent, and ceramic powder.
5. A ceramic green sheet obtained by using the slurry for ceramic green sheet according to claim 4.
6. A multilayer ceramic capacitor obtained by using the ceramic green sheet according to claim 5.
Citation Information
Patent Citations
Polyvinyl acetal resin for ceramic green sheet, slurry composition, ceramic green sheet, and laminate ceramic condenser
JP2011236304A
Intermediate film for laminated glass, multilayer intermediate film for laminated glass, and laminated glass
JP2015147729A
JPP7457853B
Polyvinyl acetal resin, slurry composition prepared therefrom, ceramic green sheet, and multilayer ceramic capacitor
WO2012023517A1
Resin film for bonding to glass plate, glass plate-containing laminate, and method for producing resin film for bonding to glass plate
WO2016052673A1